The Relationship Between Passing Accuracy and On-Point Passing Skills Among Amateur Club-Level Volleyball Players - Priatmojo, Hanif Setyo; Utamayasa, I Gede Dharma; Kusuma, Angga Indra; Hadi, Santika Rentika; Hayati; Epostam, Adim Batuhan Soyadim Onay; Zen, Mohammad Zaim (Universitas Negeri Surabaya, 2026)
Purpose: Passing accuracy is an essential technical skill in volleyball that determines the effectiveness of team attacks and game organization. However, many developing athletes still experience difficulties in maintaining accurate and consistent passing performance. Therefore, this study aims to analyze the relationship between passing accuracy and on-point passing skills among Kendal Sewu volleyball players. Materials and Methods: This study employed a descriptive approach involving 12 active volleyball players from the Kendal Sewu Volleyball Club aged between 15 and 25 years. Data were collected using a questionnaire consisting of 24 items designed to measure passing accuracy and on-point passing performance. Observations during training sessions were also conducted to support the data. Instrument validity and reliability were tested using item-total correlation and Cronbach’s Alpha with SPSS software. Result: The findings indicate that most players still demonstrate inconsistent passing accuracy during training sessions and gameplay situations. Only a small proportion of players showed adequate on-point passing performance, while the majority experienced difficulties in directing passes accurately toward teammates. These findings suggest that technical mastery, coordination, and training variation may influence passing performance. Conclusion: Passing accuracy plays a crucial role in building effective offensive strategies in volleyball. The results highlight the importance of structured and varied training programs to improve passing precision and overall team coordination among Kendal Sewu volleyball players.